PENGARUH PENGGUNAAN KAPUR BAKAR DAN KAPUR GILING (MILL) TERHADAP KUAT TEKAN SPESI - Endaryanta, Endaryanta (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Burned and raw limestone powder is a kind of binder that has been widely used in traditional construction of masonry and clay brick wall. Nowadays, limestone powder also widely used in many construction projects as a portland cement admixture. This research is designed to examine the effects of burned and raw limestone powder on the compressive strength of mortar. This research has been done with experimental method using various composition in mortar mix design. The compositions that used in this research are 1:1/4:3, 1:3/4:3, 1:1:3 and 1:2:3 of portland cement, limestone powder and sand, with six standard cubes for each average of mortar compressive strength, that have been tested in the Laboratory of Building Material, Department of Civil Engineering and Planning Education, Faculty of Engineering in State University of Yogyakarta. Test results indicate that (a) average of mortar compressive strength using 1:1/4:3 composition of portland cement, limestone powder and sand is 24,79 MPa for burned limestone powder and 16,3 MPa for raw limestone powder, (b) average of mortar compressive strength using 1:3/4:3 composition of portland cement, limestone powder and sand is 14,14 MPa for burned limestone powder and 13,28 MPa for raw limestone powder, (c) average of mortar compressive strength using 1:1:3 composition of portland cement, limestone powder and sand is 12,28 MPa forburned limestone powder and 7,78 MPa for raw limestone powder, (d) average of mortar compressive strength using 1:2:3 composition of portland cement, limestone powder and sand is 8,56 MPa for burned limestone powder and 7,18 MPa for raw limestone powder, (e) There is a significant difference of mortar compressive strength using burned limestone powder and raw limestone powder, (f) the use of burned limestone powder as portland cement admixture is better than raw limestone powder that indicated from the result of compressive strength tests. Keywords: nlortar, conzpressive strength, lilnestone po vder.